2006
DOI: 10.1007/s11187-006-9011-4
|View full text |Cite
|
Sign up to set email alerts
|

The Resource-Based Theory of the Firm and Firm Survival

Abstract: firm survival, resource-based theory, hazard rates, manufacturing, technological opportunity., C41, L1, L26, L60,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
143
5
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(182 citation statements)
references
References 38 publications
(42 reference statements)
24
143
5
6
Order By: Relevance
“…Therefore, these agents are interested to know how likely a firm is to survive, what determines firm exits, and whether there is a "shadow of death" visible already some time before a firm finally closes down, thus making preventive actions possible. Although there is some literature on the determinants of firm exits (e.g., Disney et al, 2003 for the UK; Bernard and Jensen, 2007 for the United States; Bellone et al, 2008 for France;Box, 2008 for Sweden;Esteve-Pérez and Mañez-Castillejo, 2008 for Spain; Fackler et al, 2013 for Germany), much less is known about the processes taking place before closure. In order to fill this research gap, this article analyzes whether firm closures occur suddenly and unexpectedly or whether employment processes can be observed that indicate an upcoming closure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these agents are interested to know how likely a firm is to survive, what determines firm exits, and whether there is a "shadow of death" visible already some time before a firm finally closes down, thus making preventive actions possible. Although there is some literature on the determinants of firm exits (e.g., Disney et al, 2003 for the UK; Bernard and Jensen, 2007 for the United States; Bellone et al, 2008 for France;Box, 2008 for Sweden;Esteve-Pérez and Mañez-Castillejo, 2008 for Spain; Fackler et al, 2013 for Germany), much less is known about the processes taking place before closure. In order to fill this research gap, this article analyzes whether firm closures occur suddenly and unexpectedly or whether employment processes can be observed that indicate an upcoming closure.…”
Section: Introductionmentioning
confidence: 99%
“…Firm age and size are generally positively associated with survival (Bartelsman et al 2005;Esteve-Pérez & Mañez-Castillejo 2008, cf. Shane 2003, and there are risks associated with newness as well as being a small-size firm 7 (Box 2008).…”
Section: The Structural Realm: Characteristics Of the Firmmentioning
confidence: 99%
“…According to the 'resource-based perspective' (Alsos et al 2003;Alsos & Carter 2006), firms may develop a competitive advantage through the possession of unique combinations of different resources (Esteve-Pérez & Mañez-Castillejo 2008;Chen et al 2009;Grande et al 2011), encompassing both tangible physical resources (e.g., natural resources and financial assets) and intangible human resources (e.g., competence and information networks) (Cefis & Marsili 2005;Grande et al 2011). Access to financial assets is crucial for both firm entry as well as performance and survival in the short and long term (Binks & Ennew 1996;Headd 2003;Musso & Schiavo 2008;Krasniqi 2009): 'the more own capital is available, the more successful will the small business owner be ' (van Praag 2003: 6;cf.…”
Section: The Structural Realm: Characteristics Of the Firmmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies (Agarwal and Audretsch, 2001;Cabral and Mata, 2003;Esteve-Pérez and Mañez-Castillejo, 2008;Siriopoulos and Lalountas, 2008;Holmes et al, 2010;Vaona, 2010;Giovannetti et al, 2011;Maçãs Nunes and Serrasqueiro, 2012) have analyzed the factors influencing firm survival. However, the specific approach focusing on the determinants factors of the survival of family-owned firms, in general, and family-owned SMEs, in particular, has been neglected in the literature.…”
Section: Introductionmentioning
confidence: 99%